2010
DOI: 10.4021/jocmr2010.05.289w
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, Specificity, Negative and Positive Predictive Values of Adenosine Deaminase in Patients of Tubercular and Non-Tubercular Serosal Effusion in India

Abstract: BackgroundIn India, tuberculosis is an endemic disease. Delay in diagnosis results in poor prognosis and fast spread of the disease. The objective of the present study is to look for an effective and acceptable diagnostic test, which may be helpful to initiate early treatment to improve prognosis and reduce spread.MethodsThree hundred and thirty patients with pleural, ascitic, meningeal and synovial effusion were selected and divided depending upon the etiology and the involvement of serosal membranes. Serosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 14 publications
7
33
0
Order By: Relevance
“…Its activity increased during the reproduction and response to antigenic stimulation of lymphocytes (21). Therefore, its increased concentration may be found in all fluids occurred in the zones of tuberculosis serositis (8,22), which is used in diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Its activity increased during the reproduction and response to antigenic stimulation of lymphocytes (21). Therefore, its increased concentration may be found in all fluids occurred in the zones of tuberculosis serositis (8,22), which is used in diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [20] observed that ADA levels in nontuberculous disease rarely exceeded the cut-off value; set for tuberculous disease. They [21] have further observed that ADA estimation is not only a fairly sensitive and specific test (more than 90 %), helpful in differentiating tubercular from non-tubercular etiology; both in pulmonary and extra-pulmonary disease but is also simple, inexpensive and rapid. For these reasons this test may help in early diagnosis, improve the prognosis and reduce spread of disease and sequelae.…”
Section: Discussionmentioning
confidence: 96%
“…This was similar to the studies carried out by Malla et al and Rajesh B et al 6,12 History of contact with tuberculosis was present in 36% of cases, similar to studies presented by Gupta BK et al and Gurses et al (42%). 13,14 However Waecker and Connor reported that an adult source of contact was identified in 70% of cases of children with CNS TB. 15 Thus, it is important that the patients should be questioned persistently about contact with a person with TB and that family members should be examined for TB, especially because of the delay from development of symptoms to diagnosis of TBM.…”
Section: Clinical Profilementioning
confidence: 99%
“…13 The protective efficacy of BCG vaccination is not known and ranges from 0 to 80%. 16 However, it has been stressed that in childhood, the vaccination protects against serious complications, such as TBM.…”
Section: Clinical Profilementioning
confidence: 99%